2018
DOI: 10.1097/md.0000000000013017
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics in patients with upper third gastric cancer following radical surgical treatment

Abstract: The incidences of upper third gastric cancer (UTGC) have been increasing. However, the prognostic factors for UTGC following radical surgical treatment remains largely unknown. This study was to investigate prognostic factors for overall survival (OS), lymph node metastasis and recurrence of UTGC.Clinicopathologic data of 126 UTGC patients who underwent radical surgical treatment were retrospectively analyzed. OS and univariate analysis were determined by Kaplan–Meier analysis and the significance of the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In present study, we found that 5-year OS for patients with UTGC, MTGC and LTGC were 35.0%, 43.2% and 51.4% respectively. We confirmed our previous study showing that 5-year OS was 38.6% for 126 patients with UTGC following radical surgical treatment in Chinese population [ 8 ] . We further extended the previous study by comparing the clinicopathologic characteristics and prognosis in patients with UTGC, MTGC and LTGC respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In present study, we found that 5-year OS for patients with UTGC, MTGC and LTGC were 35.0%, 43.2% and 51.4% respectively. We confirmed our previous study showing that 5-year OS was 38.6% for 126 patients with UTGC following radical surgical treatment in Chinese population [ 8 ] . We further extended the previous study by comparing the clinicopathologic characteristics and prognosis in patients with UTGC, MTGC and LTGC respectively.…”
Section: Discussionsupporting
confidence: 91%
“…[ 7 , 14 , 15 ] The prognostic significance of depth of invasion and lymph node metastases in GC was also previously reported. [ 8 , 14 , 16 – 18 ] To examine the influence of separate tumor locations on the survival outcome of GC patients, we divided the 542 GC patients into UTGC, MTGC and LTGC groups and compared the clinicopathologic characteristics and prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qinghai Province is located in the North-Western China and one of the provinces having the highest incidence and mortality of GC in China. [ 2 ] We previously analyzed the clinicopathologic characteristics and prognosis of GC patients with different tumor locations in Qinghai Province and found that GC in upper third of the stomach is distinct from the lower third GC whereas middle third GC shares some characteristics from both upper third GC and lower third GC. [ 10 ] However, few studies reported the incidence and prognosis of young GC in the province.…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel is a new anti-tumor drug, which acts on G2/M phase of tumor cells, promotes tubulin polymerization, inhibits its depolymerization, and finally forms stable non-functional microtubules, thus inhibiting the mitosis of tumor cells and promoting apoptosis of tumor cells. [5] Frei et al [6] proposed and began the first neoadjuvant chemotherapy including paclitaxel for cervical cancer in 1982. Several studies have showed that neoadjuvant chemotherapy has a good therapeutic effect on high-risk cervical cancer with adverse prognostic factors, that is, locally advanced cervical cancer, stage Ib2–IIa massive cervical cancer, and early parametrial invasion of stage IIB.…”
Section: Introductionmentioning
confidence: 99%